DAYA SAING UNGGUL MELALUI LOYALITAS DAN MARKETING 3.0 SERTA DIMENSI INOVASI PADA PROGRAM PASCASARJANADI JAKARTA - Susilo, Wilhelmus Hary (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2015)
A concept is developed from the marketing 3.0 towards achieving the competitiveness higher educationÃ‚Â in Jakarta. This research conducts the hybrid models of marketing 3.0 on model structural equation. Thesample used in this study are 105 post graduate students at 3 institutions.The findings of this research suggestsÃ‚Â hybrid models marginal fit with the chi-square = 420.7, GFI = .73 and CFI = .97. Hypothesis that confirmsÃ‚Â pertains; influence communitization of the decision by the purchase (t = 3.69), influence building character ofÃ‚Â competitiveness (t = 5.72), communitization influence on competitiveness (t = 2.80 , the decision the purchaseÃ‚Â of loyalty (t = 2.80) and marketing 3.0 any impact, the purchase, and loyalty simultaneously on competitivenessÃ‚Â institutions with R2 = .98 .Then the dimensions; encouragement and action purchase of purchase variableÃ‚Â decision that deals with dimensions; innovation, purchase repeated, resistant to competitors, recommended andÃ‚Â buy other line of the loyalty, with an r ( er )value = .99 .Keywords: competitiveness, loyalty, marketing 3.0, innovations